2022
DOI: 10.1038/s42003-022-03997-3
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent binding kinetics resolved by fluorescence proximity sensing

Abstract: Multivalent protein interactors are an attractive modality for probing protein function and exploring novel pharmaceutical strategies. The throughput and precision of state-of-the-art methodologies and workflows for the effective development of multivalent binders is currently limited by surface immobilization, fluorescent labelling and sample consumption. Using the gephyrin protein, the master regulator of the inhibitory synapse, as benchmark, we exemplify the application of Fluorescence proximity sensing (FP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…Recent studies have reported that tumour progression, loss-of-heterozygosity, and deregulation of WNT signalling are indeed affected by the length of the remaining tumour suppressor (Albuquerque et al, 2002). Furthermore, aberrant WNT signalling, caused by APC truncation, is a prerequisite for the establishing of a super competitor cell, manifesting CRC onset (Flanagan et al, 2021b; Schulte et al, 2022; van Neerven et al, 2021). Despite our growing understanding of the underlying genetic causalities of colorectal cancer, the identification of mechanisms at the basis of this phenomenon and identification of suitable therapeutic targets presents a challenge that yet needs to be overcome (Guren, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that tumour progression, loss-of-heterozygosity, and deregulation of WNT signalling are indeed affected by the length of the remaining tumour suppressor (Albuquerque et al, 2002). Furthermore, aberrant WNT signalling, caused by APC truncation, is a prerequisite for the establishing of a super competitor cell, manifesting CRC onset (Flanagan et al, 2021b; Schulte et al, 2022; van Neerven et al, 2021). Despite our growing understanding of the underlying genetic causalities of colorectal cancer, the identification of mechanisms at the basis of this phenomenon and identification of suitable therapeutic targets presents a challenge that yet needs to be overcome (Guren, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the interaction and map the USP10 binding site required for β-Catenin interaction, we conducted a µSPOT protein binding assay (Schulte et al, 2022). Here, the intrinsically disordered regions (IDR) of USP10, along with the IDR sequences of a known β-Catenin binder, USP7 (Novellasdemunt et al, 2017), and an additional DUB comprised of large unstructured regions, USP36 were displayed as overlapping peptide libraries and probed with recombinant β-Catenin (Figure 3E).…”
Section: Truncation Of Apc Allows For De Novo Protein-protein Interac...mentioning
confidence: 99%
“…This was achieved using the minimal iFSP1 pharmacophore with a piperazine group (iFSP1-Pip) as an exit vector protruding from the FSP1 binding pocket (Fig. 4A) for conjugation to a SulfoCyanine5 [22]. The resulting fluorescent tracer "FSP1-Tracer" enabled the detection of FSP1 binding and further highlights the precursor as starting point for the design of advanced iFSP1-based effectors.…”
Section: Fsp1-tracer Determines Ifsp1 Affinity and Ligand Bindingmentioning
confidence: 99%
“…To con rm the interaction and map the USP10 binding site required for β-Catenin interaction, we conducted a µSPOT protein binding assay 29 . Here, the intrinsically disordered regions (IDR) of USP10, along with the IDR sequences of a known β-Catenin binder, USP7 12 , and an additional DUB comprised of large unstructured regions, USP36 were displayed as overlapping peptide libraries and probed with recombinant β-Catenin (Fig.…”
Section: Truncation Of Apc Allows For De Novo Protein-protein Interac...mentioning
confidence: 99%